The international athlete - advances in management of jet lag disorder and anti-doping policy - Herman, D.; MacKnight, J. M.; Stromwall, A. E.; Mistry, D. J. (Clinics in Sports Medicine, 2011)
To perform at the highest level of international competition, athletes need to maximize rest during long travel, and expeditiously overcome the detrimental effects of "jet lag" (JL). The negative effects of JL may be alleviated by adopting a multimodality approach, including the judicious use of melatonin and other pharmacologic agents to aid re-entrainment and improve sleep characteristics. Strict compliance with anti-doping policy is pivotal before and during competition. There have been several recent updates regarding the use of selected medications, which mandate constant vigilance by sports medicine personnel to both evaluate drug efficacy and judiciously prescribe approved medications. It is critical that medical staff maintain familiarity and awareness on a continual basis to effectively educate athletes and support staff.